Genetic Basis for Saccharomyces cerevisiae Biofilm in Liquid Medium. Issue 9 (1st September 2014) - Andersen, Kaj Scherz; Bojsen, Rasmus; Sørensen, Laura Gro Rejkjær; Nielsen, Martin Weiss; Lisby, Michael; Folkesson, Anders; Regenberg, Birgitte
Abstract: Biofilm-forming microorganisms switch between two forms: free-living planktonic and sessile multicellular. Sessile communities of yeast biofilms in liquid medium provide a primitive example of multicellularity and are clinically important because biofilms tend to have other growth characteristics than free-living cells. We investigated the genetic basis for yeast, Saccharomyces cerevisiae, biofilm on solid surfaces in liquid medium by screening a comprehensive deletion mutant collection in the Σ1278b background and found 71 genes that were essential for biofilm development. Quantitative northern blots further revealed that AIM1, ASG1, AVT1, DRN1, ELP4, FLO8, FMP10, HMT1, KAR5, MIT1, MRPL32, MSS11, NCP1, NPR1, PEP5, PEX25, RIM8, RIM101, RGT1, SNF8, SPC2, STB6, STP22, TEC1, VID24, VPS20, VTC3, YBL029W, YBL029C-A, YFL054C, YGR161W-C, YIL014C-A, YIR024C, YKL151C, YNL200C, YOR034C-A, and YOR223W controlled biofilm through FLO11 induction. Almost all deletion mutants that were unable to form biofilms in liquid medium also lost the ability to form surface-spreading biofilm colonies (mats) on agar and 69% also lost the ability to grow invasively. The protein kinase A isoform Tpk3p functioned specifically in biofilm and mat formation. In a tpk3 mutant, transcription of FLO11 was induced three-fold compared with wild-type, but biofilm development and cell–cell adhesion was absent, suggesting that Tpk3p regulates FLO11 positive posttranscriptionally and negative transcriptionally. The study provides a resource of biofilm-influencing genes for additional research on biofilm development and suggests that the regulation of FLO11 is more complex than previously anticipated.